Homogeneous Observer Design for Linear MIMO Systems. Issue 2 (2020) - Zimenko, Konstantin; Polyakov, Andrey; Efimov, Denis; Kremlev, Artem
Abstract: The paper is devoted to the problem of state observation (particularly, in finite time) of linear MIMO systems. The presented nonlinear observer does not require system transformation to a canonical form and guarantees finite-time (asymptotic with a fixed-time attraction of any compact set containing the origin) stability of observation error equation if homogeneity degree is negative (positive). The proposed observer is robust in input-to-state sense with respect to disturbances and measurement noises. Performance of the observer is illustrated by a numerical example.